ISLAM DAN SEKULERISME DALAM DUNIA PENDIDIKAN DI INDONESIA - Dede Misbahul Alam; Silvia Nuryani; Safna Devy (STKIP Subang, 2026)
This research addresses the modern debate between Islam and secularism regarding religious freedom and the role of religion in the state. The purpose of this study is to clarify misunderstandings held by secular scientists about Islam and to improve the understanding of religion’s role in public life. Utilizing a descriptive- comparative approach through literature review, this study examines definitions from various figures and Islamic sources. The results indicate that Islam and secularism are fundamentally different and often contradictory concepts. Islam is a comprehensive (syumul) and perfect (kaffah) religion that regulates all aspects of life, including law and politics. Conversely, secularism separates religion from the state and limits it to the private sphere. While countries like Indonesia adopt a unique system that blends these elements, the study concludes that secularism opposes the implementation of Sharia. To resolve these tensions, secularists are encouraged to study Islam from its original sources, namely the Quran and Hadith.